Achieving Education for All in Post-Conflict Cambodia - Thomas, Christopher J. (World Bank, Washington, DC, 2012)
Cambodia has made good progress in rebuilding its education system after three decades of conflict and isolation. Enrollments are growing, administration is improving, and large numbers of schools have been rehabilitated. A number of innovative and mutually reinforcing programs have energized local administrators and resourced schools, building on early efforts to rebuild capacity. These are, however, not sufficient conditions for improving education outcomes, and significant challenges remain in the financing and management of education in order to realize Cambodia's goal of providing free, universal access to basic education.